ANALISIS PENGARUH KELAYAKAN PENILAIAN KREDIT (ANALISIS 5C) TERHADAP RESIKO KREDIT MIKRO (Studi Empiris pada Seluruh Bank Konvensional yang Terdapat di Kota Pekanbaru) - Sri Rahmi Utami; Taufeni Taufik; Yuneita Anisma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This research is to investigate the influence of credit ratings feasibility analysis (5C analysis) on the risk of micro credit. The population in this research is all credit analysts of all conventional banks in Pekanbaru city. Sample of this research is all population that is all credit analysts of all conventional banks in Pekanbaru city which amounts to 47 people. Data collection techniques used by distributing questionnaires. Data analysis method used in this research is multiple regression with SPSS version 17. The results of this research indicates that the characters significantly affect the risk of micro-credit with 2.342 t-test, t-table 2.020 and 0.024 significant value. Significant capacity with micro-credit risk, with 4.953 t-test, t-table 2.020 and 0.000 significant value. Collateral significantly affect the risk of micro-credit, with 3.427 t-test, t-table 2.020 and significant value of 0.001. Capital does not significantly influence the risk of micro-credit, with 1.039 t-test, t-table 2.020 and 0.305 significant value. Condition of economy does not significantly influence the risk of micro-credit, with 1.336 t-test, t-table 2.020 and 0.189 significant value. The value of Adjusted R Square of 0.885. This means that 88.5% micro-credit risk variable can be explained by the character, capacity, collateral, capital, and condition of economy. While the remaining 11.5% is explained by other variables outside of this research.Keywords : Credit ratings, 5C analysis and the risk of micro credit